1988
DOI: 10.1002/eji.1830180802
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte‐macrophage colony‐stimulating factor‐cultured bone marrow‐derived macrophages reveal accessory cell function and synthesis of MHC class II determinants in the absence of external stimuli

Abstract: The antigen-mediated activation of a number of T cell clones by bone marrow (BM) cells cultivated in the presence of various colony-stimulating factor (CSF) preparations was investigated. BM macrophages (BMM phi) grown in L929 cell supernatant as a crude source of macrophage colony-stimulating factor (M-CSF) as well as BM cells propagated in the presence of recombinant M-CSF exhibited transient antigen presentation potential to some T cell clones, being maximal on day 7 and having declined to a low level by da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Macrophages were grown from femoral bone marrow cells of BALB/c and BALB.K mice by culture for 6 days in culture medium supplemented with 5% of a supernatant from the L929 cell line as a source of macrophage colony stimulating factor, as described previously (41). Macrophages were activated by treatment overnight with 1 ng/ml interferon-␥ (R&D Systems, Abingdon, UK) before use in antigen presentation assays.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages were grown from femoral bone marrow cells of BALB/c and BALB.K mice by culture for 6 days in culture medium supplemented with 5% of a supernatant from the L929 cell line as a source of macrophage colony stimulating factor, as described previously (41). Macrophages were activated by treatment overnight with 1 ng/ml interferon-␥ (R&D Systems, Abingdon, UK) before use in antigen presentation assays.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow cells from femurs of BALB/c mice were differentiated into macrophages [7 days with media supplemented with 5% horse serum (Sigma-Aldrich) and 10% L929 supernatant, 34 (refreshed on days 3 and 6) or DC (10 days with media supplemented with 20 ng/ ml granulocyte-macrophage-colony-stimulating factor 35 (PreproTech, Inc. Rocky Hill, NJ) (refreshed on days 3, 6 and 8)]. Macrophages were activated with 100 ng/ml interferon-c (IFN-c) …”
Section: Cell Lines and Culturementioning
confidence: 99%
“…Although the mechanisms of class II antigens expression on colonic epithelia are unclear, it has been shown that cytokines, such as IFN-y (Carrel et (Crawford et al 1987), and granulocyte/ macrophage-colony stimulating factor (Falk et al 1988 ;Fischer et al 1988), have the ability to induce expression of class II antigens on various human cells . Therefore, these cytokines might also induce expression of class II antigens on colonic epithelia.…”
Section: Discussionmentioning
confidence: 99%